HUBUNGAN KEKUATAN OTOT LENGAN DENGAN KETEPATAN SERVIS BAWAH OLAHRAGA BOLA VOLI PADA SISWA KELAS VIII SMPN 3 WATES KABUPATEN KEDIRI - KARJITO, KARJITO (Universitas PGRI Adi Buana, 2019)
The study is done for the muscular strength of relations arm with the accuracy of serve down in the game of volleyball to their students the son of the eighth grade SMPN 3 Wates. The study aims to know is there a relationship with the power of the arm musclas to their students the son of the eighth grade to do under the accuracy of serve in the game of sport branch volleyball. A problem in the formulation of this research is the relationship has the power of the arm muscles with the accuracy of serve down in the game of the branch of sport volleyball on students the son of a class of eight SMPN 3 Wates. The research is research the is non experimentation and the use of the study or kolerasional product-moment correlation. The subject of this research is the son of a class of 30 students, data collection techniques used in tests. Based on the above data analysis hes been obtained that r count of more large table to r. and with r count of 0,966 r table with 0,361 is significant leve of 5%. With the hypothesis said there is a muscular power arm with the accuracy of serve down in a game of volleyball sports can be accepted, can be concluded so that a significant relation exists between the power of the arm muscles with the accuracy of serve down in game of volleyball in sports the son of a class of eight students SMPN 3 Wates. Key Words: The power of the arm muscles, the accuracy of serve under.